Komunikasi pemasaran terpadu dan warisan merek: Pendekatan strategis untuk meningkatkan minat kunjungan museum di Indonesia - Paulus Hermien Sarjana; Harliantara Harliantara; Nur Annafi Farni Syam Maella (Universitas Kristen Maranatha, 2025)
This study tests the integrated marketing communication (IMC) strategy on visit intention in Indonesia. This study also aims to test the effect of IMC on brand heritage and the mediation effect of brand heritage on IMC and interest in visiting museums. The sample in this study was 240 respondents. Data was collected by distributing questionnaires online via Google Forms and processed using the SEM model with AMOS software. The results of the study showed that IMC had a positive effect on the intention to visit museums. Effective IMC (including advertising, direct promotion, direct marketing, public relations, WOM, events and experiences, and interactive marketing) can increase the intention to visit museums in Indonesia. In addition, the study's results prove the positive effect of IMC on brand heritage and the effect of brand heritage on interest in visiting museums. This study also found that brand heritage can mediate IMC and interest in visiting museums. The results of this study are expected to help museum owners and managers have the right and effective IMC strategy to increase tourist interest in visiting museums. The right IMC strategy will also increase brand heritage and interest in visiting museums.